Pelatihan Echogreen Pemanfaatan Limbah Daun Kopi menjadi Teh Celup Daun Kopi - Masyadi, Masyadi; Amrial, Amrial; Patappari, Andi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Mattabulu Village's coffee farmers struggle with a lack of product diversification, which also affects their understanding of how to make coffee leaf tea correctly and effectively. As a result, the outcomes are unsatisfactory and not well received by consumers. The large coffee plantations produce coffee leaf waste, which farmers usually burn to reduce feces; however, this leads to air pollution. To help solve the existing problems, a community service initiative was carried out in the form of echogreen training on the utilization of coffee leaf waste into coffee leaf tea bags. This community service activity aims to transform coffee leaves into a marketable product by verifying the processing of coffee leaves. The methods implemented are socialization, training, evaluation, and mentoring. The training and mentoring materials consist of enhancing the skills of the Mattabulu coffee business group in product diversification, particularly in producing coffee leaf tea bags with better quality that can be sold commercially and digitally. In addition, it can also be socialized that coffee leaf tea bags have health benefits because they contain less caffeine compared to coffee. Coffee leaf tea can prevent cardiovascular problems and heart disease due to the presence of mangiferin, which can lower blood pressure. During the event, the community and members of the Mattabulu coffee business group warmly welcomed the DPL team and students. It is hoped that in the future, the coffee leaf tea bag product will have good prospects for community income, supported by the availability of raw materials, the ease of product processing, and the availability of equipment that has already been provided to the business group.